Strategi Pengembangan Lembaga Pendidikan Islam di Daerah Minoritas Muslim dan Kawasan Elite - Faisol Hakim (STAIFAS-Press, 2020)
Islamic educational institutions or islamic boarding school from the very beginning were founded with the principle of a reason approach rather than a hegemony of power and violence, in contrast to outside Islam which leads to spread based on linear fikiq law with just one legal view. Unlike the development of Islam or Islamic boarding schools in Indonesia through a more refined and high appreciation approach to education and Sufism, with that the Indonesian people of Java specifically can accept Islam with the principle of Sendiko Dawuh Gusti, to the Kings of Java at that time, and in line with the philosophy of Java that did not exist one that is contrary to Islam and answers the challenges of the times, discussion of the folklore of Javanese